Influence of different application rates of FGD gypsum and aeolian sand on CO2 and N2O emissions from cotton-capsicum saline-alkali soil - Chen, Yiwei; Luo, Fan; Guan, Yao; He, Xinghong; Wang, Jian; Fan, Debao; Gao, Rui (Frontiers in Environmental Science, 2024)
In order to reveal the response of soil CO2 and N2O emissions to alkaline agricultural soil amendments under the cotton field-pepper crop system, six treatments (blank treatment (CK) desulfurized gypsum 15 t/hm2 (LH), desulfurized gypsum 30 t/hm2 (LA), desulfurized gypsum 15 t/hm2 and aeolian sand 15 t/hm2 mixed application (FL), aeolian sand 15 t/ hm2 (FH), and aeolian sand 30 t/hm2 (FA)) on soil CO2 and N2O emission fluxes. The results showed that FGD gypsum and aeolian sand significantly increased soil moisture and soil nutrients during the cotton fertility stage, and the water retention effect of LA treatment was the best; in the cotton-chilli pepper cropping system, the aeolian sand decreased the nitrate nitrogen content of the cotton field soil, and FGD gypsum decreased the nitrate nitrogen content of the chilli pepper soil;FH and FA treatments reduced the conductivity of cotton and pepper soils. The cumulative soil CO2 emission fluxes of cotton field and pepper under different treatments of alkaline farmland were 3528.21~8861.06 kg/hm2 and 2909.63~7960.34 kg/hm2, respectively. Compared with CK, the cumulative soil CO2 emission fluxes of cotton field were reduced by 31.69%~60.18%, respectively, while the cumulative soil CO2 emission flux was reduced by 36.02%~63.45% in chilli pepper, respectively. The cumulative soil N2O emission fluxes of cotton and pepper alkaline farmland under different treatments were 0.35~0.62 kg/hm2 and 0.16-0.41 kg/hm2, respectively. Compared with CK, the cumulative soil N2O emission fluxes of cotton were reduced by 19.61%~43.89%, while those for chilli were reduced by 33.47%~ 60.59%, respectively. Among them, the inhibition effect of soil CO2 and N2O cumulative emission in cotton field reached a significant level in FA treatment. Compared with CK, the application of FGD gypsum and aeolian sand reduced the integrated greenhouse effect of both cotton field and chilli crop, of which the combined greenhouse effect of the FA treatment was at the lowest level in both the cotton-chilli cropping systems. Therefore, after comprehensively analyzing the effects of different treatments on the physicochemical properties and gas emissions of saline soils, the FA treatment had the best effect on suppressing CO2 and N2O emissions and improving soil physicochemical properties.